Colonial and post colonial philosophies of Islamic education from the perspective of philosophy of engagement - House, Yousef Rahath (Institute of Education, International Islamic University Malaysia, 2011)
The ultimate purpose of this study is to contribute a new perspective to the Islamic educational philosophy that is rooted in the socio-political dimension of Islam in order to actualize the notion of empowerment in the Islamic educational practice. In line with this view, the present study examines the colonial and post-colonial Islamic educational philosophies with regards to their capability to empower Muslims to act in and on the world. The study's central concern is to highlight aspects that have been neglected in Islamic educational practice and suggest new dimensions that should be adopted. The procedure employed is philosophical and historical analysis, attempting to develop a new conceptual framework which can be called philosophy of engagement or the notion of empowerment as acting in and on the world. The notion of acting in and on the world represents two dimensions of social action; act in means to make an effort to understand the society in order to transform it whereas act on refers to the attempt to use this understanding to transform the social conditions into a more just one. Hence the conceptual model of evaluation suggests that education should be viewed as a social process that helps students gain control over their own lives by being allowed to act on issues they define as important. Education must be viewed as a process that provides fundamental freedom and resources to understand the world and grants the ability to change that world. The study provides Islamic justification for the relevance of the notion of empowerment as acting in and on the world in the Islamic education. Based on this, colonial and post-colonial philosophies of Islamic education are evaluated to see to what extend these philosophies correspond with the conceptual framework proposed by this thesis. The study indicates that a number of changes are needed in Islamic educational practice which would emphasise the notion of act in and on the world in order to change the Islamic world. It has been suggested that by making a close link between social realities and educational process, the notion of empowerment can be realized.